(untitled) - Riggs, Ransom; Cassandra Jean (New York, New York, 2013)
After a family tragedy, Jacob feels compelled to explore an abandoned orphanage on an island off the coast of Wales, discovering disturbing facts about the children who were kept there.
Accelerated Reader
Keywords: Ghost stories; Horror fiction; Graphic novels